If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16b + 4 = 0 Reorder the terms: 4 + 16b = 0 Solving 4 + 16b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 16b = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 16b = 0 + -4 16b = 0 + -4 Combine like terms: 0 + -4 = -4 16b = -4 Divide each side by '16'. b = -0.25 Simplifying b = -0.25
| -59+9x=26+4x | | 8n-21=-5 | | 5-3t=11 | | (-6p)+5=-1 | | f(n)=(5n+1)2 | | -81+5x=93-x | | -x+9=-7-5x | | 2=v-3/3 | | 1/5x-3=4 | | -5w^2+8=0 | | T/-2=18 | | 2(2x+5)-3=-3(x-1) | | 3x-2/3=7 | | 2x+9y-36=180 | | c(x)=x-4/x^2-16 | | -17=n-20 | | 4nm-4m=8 | | 17+2n=2n+21 | | 24=(3-n)+5 | | 1w=-11 | | x-18.1=-0.7 | | 0.01(1)+0(-0.5)=0.02(-0.5)+1 | | 6x+55=3x+244 | | m^3=8/125 | | j-3/2=2 | | -8+3.5=1-4(3.5) | | -3n+18=-6(n+1) | | 12x-34=46+7x | | 12b=.2 | | (6g-9)+1/3(15-9g)= | | 12+3d=d | | 5.7+b=23 |